MENGEVALUASI KINERJA PASCA PENGAWETAN DAN PENYIMPANAN UBI JALAR MALAYSIA, VitAto - Maulana, Lutvi; Hanif, Andini; Samsiah, Samsiah; Ismawaty, Noor (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Sweet potatoes, particularly the VitAto variety, are well-known for their richness in beta-carotene and vitamin C, making them a potential source of nutritious food. However, post-harvest preservation and storage remain significant challenges as they can affect the produce's quality, taste, and nutritional content. Therefore, evaluating the preservation and storage of VitAto sweet potatoes is crucial to extend their shelf life and minimize post-harvest losses, thereby supporting local food security.The objective of this study was to evaluate the post-preservation and storage performance of VitAto sweet potatoes during the storage period. The study employed a quantitative approach to assess the effectiveness of preservation and storage methods. Sweet potato samples were randomly selected based on uniform criteria and preserved using drying, waxing, and natural preservatives. The samples were stored under various conditions (room temperature, refrigeration, humidity, and storage duration) and evaluated based on their physical, chemical, and organoleptic qualities.The results showed that an 8-week storage period caused significant changes in VitAto sweet potatoes. Moisture content decreased, weight loss increased up to 11.28%, and total soluble solids (TSS) rose from 12.08 Brix to 17.46 Brix. The skin color changed, with increased redness (a*) and yellowness (b*), while the flesh color remained stable until week six before lightness (L*) began to decline. The pH values, as well as Chroma and Hue parameters, remained relatively stable. These changes reflect physiological and biochemical processes during storage, providing valuable insights for optimizing shelf life and maintaining the quality of VitAto sweet potatoes